The Impact of Bank Service Quality on Satisfaction that Impacts Word of Mouth Promotion - Zaenal Aripin; Vip Paramarta; Kosasih; Didin Saepudin; Farida Yuliaty; Fitriana (Syntax Corporation Indonesia, 2023)
Beckground: In the banking industry, service quality is an important factor in maintaining and increasing customer satisfaction. One indicator of the success of service quality is word of mouth by satisfied customers. However, there is still little in-depth research on the impact of bank service quality on customer satisfaction that impacts word of mouth. Aims: This study aims to analyze the impact of bank service quality on customer satisfaction and identify how customer satisfaction contributes to word of mouth in the context of the banking industry. Research Methods: This study used a qualitative approach with in-depth interviews as the data collection technique. The respondents were bank customers who have used the bank's services in the recent period. The collected data were analyzed using content analysis techniques to identify themes and patterns in customer responses. Results and Conclussion: This study used a qualitative approach with in-depth interviews as a data collection technique. The respondents were bank customers who have used the bank's services in the last period. The collected data were analyzed using content analysis techniques to identify themes and patterns in customer responses. Contribution: This study uses a qualitative approach with in-depth interviews as a data collection technique. The respondents of this study are bank customers who have used bank services in the last period. The collected data were analyzed using content analysis techniques to identify themes and patterns in customer responses.